Zagłada w Danii: kwestia badań i pamięci - Goldbaum Tarabini Fracapane, Silvia (Zagłada Żydów. Studia i Materiały, 2007)
The article deals with the most important events of the Holocaust in Denmark. The first part outlines the broader historical context of the events of October 1943 and the deportation of Danish Jews. It also contains a critical comment on the mainstream historical narration, particularly those aspects that concern the situation of Jewish prisoners at Theresienstadt. The second part is an overview of the latest research into the Danish aspects of the Holocaust, such as the expulsion of Jewish refugees, the rescue operation of October 1943, and the actual number of deportees. The author also presents results of her own research of the Danish remembrance culture.